THE EFFECT OF GOVERNMENT INVESTMENT AND EXPENDITURES ON CITY POPULATION GROWTH IN SOUTH SULAWESI PROVINCE - Nurul Awaliah; Madris Madris; Sabir Sabir (Jurnal Ekonomi, 2022)
This study aims to determine the effect of investment and government spending on urban population growth, both directly and indirectly through employment opportunities. This study uses panel data with 6 districts/cities in South Sulawesi Province for the 2010-2021 period. The analysis model used is Regression Analysis with SPSS software. The results of this study indicate that simultaneously investment and government spending affect the growth of the urban population. Likewise with investment, government spending, and employment opportunities simultaneously affecting the growth of the urban population. Partially, investment has a positive effect and government spending has a negative effect on urban population growth. Meanwhile, investment and government spending have a positive effect, but employment opportunities have a negative effect on urban population growth. As for the indirect effect, investment has a negative effect on urban population growth through employment opportunities and government spending has a positive effect through employment opportunities in urban areas of South Sulawesi Province.